Interdisciplinary modeling and participatory simulation of forest management to foster adaptation to climate change. (May 2022) - Fouqueray, Timothée; Latune, Julie; Trommetter, Michel; Frascaria-Lacoste, Nathalie
Abstract: The adaptive capacity of forests and foresters to overcome the adverse effects of climate change remains highly uncertain despite intense research efforts. While foresters are often invited "not to put all their eggs in one basket, " adaptation strategies to climate change mostly depend on silvicultural diversification. To explore how socioeconomic adaptive tools can complement these technical evolutions in forestry, we designed an interdisciplinary and participatory simulation of forest management combining a role-playing game, ecological models of forest evolution, and a severe climate change scenario. Participants from French natural parks and forest organizations responded positively to its multiple applications. Here, we investigate the technical and timber-focused framing of climate change by forest managers. We also analyze participants' negotiations when attempting to change the simulation rules of forest management. Drawing on this experience, we highlight how establishing a payment system for ecosystem services can reduce financial imbalance driven by climate change. Highlights: Interdisciplinary tool Foster Forest explores forest adaptation to climate risks. Forest management simulations are positively received by forest organizations. Participatory simulations successfully foster unregretful and economic adaptations. Economic adaptation involves shunting climate uncertainty about timber incomes. Economic adaptation induces commodifying non-provisioning ecosystem services. Collective adaptive action is steered by stakeholders with a public interest role.